Mouse models for inherited endocrine and metabolic disorders. - Piret, SE; Thakker, R (2011)
In vivo models represent important resources for investigating the physiological mechanisms underlying endocrine and metabolic disorders, and for pre-clinical translational studies that may include the assessments of new treatments. In the study of endocrine diseases, which affect multiple organs, in vivo models provide specific advantages over in vitro models, which are limited to investigation of isolated systems. In recent years, the mouse has become the popular choice for developing such in vivo mammalian models, as it has a genome that shares ∼85% identity to that of man, and has many physiological systems that are similar to those in man. Moreover, methods have been developed to alter the expression of genes in the mouse, thereby generating models for human diseases, which may be due to loss- or gain-of-function mutations. The methods used to generate mutations in the mouse genome include: chemical mutagenesis; conventional, conditional and inducible knockout models; knockin models and transgenic models, and these strategies are often complementary. This review describes some of the different strategies that are utilised for generating mouse models. In addition, some mouse models that have been successfully generated by these methods for some human hereditary endocrine and metabolic disorders are reviewed. In particular, the mouse models generated for parathyroid disorders, which include: the multiple endocrine neoplasias; hyperparathyroidism-jaw tumour syndrome; disorders of the calcium-sensing receptor and forms of inherited hypoparathyroidism are discussed. The advances that have been made in our understanding of the mechanisms of these human diseases by investigations of these mouse models are described.